Strategy for Institutionalizing Inclusive Family Quality Toward Women Civil Servants - Rini, Diana Catur; Radjab, Ridwan; Silitonga, Mala Sondang (Journal of Family Sciences, 2024)
The background to this research is that the implementation of family quality and human resource management system support is not yet optimal, especially for female civil servants. The novelty of this research is that it is a strategy for family quality that includes female civil servants in government agencies. This research aims to determine the factors that influence and strategies for the quality of family inclusion in female civil servants. Qualitative research method with a case study of female civil servants at Ministry of Women’s Empowerment and Child Protection RI (MoWECP) in October 2023 – February 2024, 7 key informants, with INVIVO Program and Gender Analysis Pathway. The results of this research are the importance of factors that influence family quality as a form of family support system. The strategy for inclusive HR management for female civil servants is the implementation of Flexible Working Arrangements (FWA), structured performance dialogue, strengthening the BerAKHLAK culture, optimal talent management, and the formation of gender working groups in agencies capable of creating a conducive work environment which is adapted to the work culture and local wisdom of each institution.